2014
DOI: 10.3389/fpsyg.2014.00553
|View full text |Cite
|
Sign up to set email alerts
|

The role of alpha-7 nicotinic receptors in food intake behaviors

Abstract: Nicotine alters appetite and energy expenditure, leading to changes in body weight. While the exact mechanisms underlying these effects are not fully established, both central and peripheral involvement of the alpha-7 nicotinic acetylcholine receptor (α7nAChR) has been suggested. Centrally, the α7nAChR modulates activity of hypothalamic neurons involved in food intake regulation, including proopiomelanocortin and neuropeptide Y. α7nAChRs also modulate glutamatergic and dopaminergic systems controlling reward p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 95 publications
0
17
0
Order By: Relevance
“…Conversely, knockdown of the α7 subunit in either cell type did not alter the feeding response to cytisine or nicotine. While α7 is highly expressed in the hypothalamus and may regulate other circuits controlling food intake (Jo, Wiedl, & Role, 2005;McFadden, Cornier, & Tregellas, 2014), based on these data, it appears to be unlikely that α7 regulates food intake in response to nicotine through AgRP or POMC neurons. Notably, our TRAP studies showed that α7 mRNA was enriched in other cell types in ARC compared with AgRP or POMC neurons, suggesting that signalling through this nAChR subtype occurs on as-yetunidentified cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, knockdown of the α7 subunit in either cell type did not alter the feeding response to cytisine or nicotine. While α7 is highly expressed in the hypothalamus and may regulate other circuits controlling food intake (Jo, Wiedl, & Role, 2005;McFadden, Cornier, & Tregellas, 2014), based on these data, it appears to be unlikely that α7 regulates food intake in response to nicotine through AgRP or POMC neurons. Notably, our TRAP studies showed that α7 mRNA was enriched in other cell types in ARC compared with AgRP or POMC neurons, suggesting that signalling through this nAChR subtype occurs on as-yetunidentified cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Following nicotine cessation, a potential target for the specific changes in carbohydrate intake seen in the present study are withdrawal-mediated decreases in serotonin. Because nAChR’s are located on serotonergic neurons and their activation increases serotonin release [94] and inhibits the production of NPY [95], removal of this inhibition following smoking cessation may lead to a compensatory increase in carbohydrate intake. Finally, orexin signaling in arcuate nucleus may be of interest, given the increase in orexin A mRNA that has been observed after NSA [96].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that nicotine, a cholinergic agonist, is capable of altering the rate of food consumption and energy expenditure, thus leading to weight changes [ 36 , 37 ]. Although the exact mechanism remains elusive, both central and peripheral mechanisms are suspected to be involved.…”
Section: Discussionmentioning
confidence: 99%